An analysis of the quality of life among diabetic foot ulcer patients in Kuantan, Pahang - Alia, Ilham; Fauzi, Muhammad Aiman; Ismail, Sarah Syahidah; Mahno, Noor Ezmas; Ahmad, Azrin Waheedy; Abdul Rahman, Mohd Norhisham Azmi; Othman, Ahmad Faidzal (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Introduction: Foot ulcer is one of the most serious complications associated with diabetes mellitus that mat resulted in a disability and impairment of health related quality of life. Materials and Methods: The main objective of this cross-sectional study was to determine the factors adversely associated with quality of life among diabetic foot ulcer patients. Diabetic patients with evidence of diabetic foot ulcer attending outpatient orthopaedics and general surgical clinic of Hospital Tengku Ampuan Afzan were recruited into this study. A set of validated SF-36 questionnaire was employed to evaluate the health-related quality of life for each patient. This study was registered with the National Medical Research Register (NMRR registration no. 17-1520-36332). Results: There is a slightly higher proportion of female among the 104 respondents. Its prevalence is most pronounces in the lower income group. Majority presented with Wagner stage 2 and 3. Amputation has been performed in 54% of these patients. Physical health score fair worse than mental health. Age, low socioeconomic status, presence of comorbidities, major amputation, ulcer at the forefoot and wheelchair usage associated with an adverse effect on the physical health aspect in these patients. Interestingly, smoker seems to score better on the mental health aspect of the quality of life. Conclusion: Diabetic foot ulcer affected physical health aspect much more than mental health aspect within the context of the quality of life.